2022
DOI: 10.1186/s12864-022-08416-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TIFY gene family in walnut and analysis of its expression under abiotic stresses

Abstract: Background Walnuts (Juglans regia L.) are known for their nutrient-rich nuts and are one of the important economic tree species in the world. However, due to global warming and soil salinization, walnuts suffer from various abiotic stresses. TIFY (TIF[F/Y]XG) proteins play an essential role in the growth and development of plants, signal transduction, and stress response in plants. At present, although the TIFY gene family of a number of plants has been identified and studied, how TIFY takes pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…This is consistent with previous studies done on walnuts, where JrTIFY14 of the JAZ subfamily positively regulated heat and salt stress in both cultivars. The study also confirmed that different tolerance walnut varieties have different Tify gene expression patterns, leading to drought, high‐temperature and salt stress resistance (Liu et al, 2022a).…”
Section: Discussionsupporting
confidence: 61%
“…This is consistent with previous studies done on walnuts, where JrTIFY14 of the JAZ subfamily positively regulated heat and salt stress in both cultivars. The study also confirmed that different tolerance walnut varieties have different Tify gene expression patterns, leading to drought, high‐temperature and salt stress resistance (Liu et al, 2022a).…”
Section: Discussionsupporting
confidence: 61%
“…Several other genes in monocots are most likely compensating for the molecular activities done by PPD genes ( Bai et al., 2011 ). Cassava, like other dicot plants, such as Populus trichocarpa , walnut ( Juglans regia ), and peach ( Prunus persica ), has members of all four subfamilies based on domain traits ( Wang et al., 2017 ; Liu et al., 2022 ; Sheng et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of maize JAZ14 in Arabidopsis may improve seedling tolerance to hormone treatments such as ABA and JA, as well as polyethylene glycol stress ( Zhou et al., 2015 ). Under salt stress, in soybean ( Glycine max ), GmTIFY10e and GmTIFY10g transgenic plants grew faster and had longer root lengths and fresh weights than wild-type plants ( Liu et al., 2022 ). Similarly, virtually all TIFY genes in rice are susceptible to a variety of abiotic stresses, and OsTIFY11a overexpression resulted in a significant increase in tolerance to salt and dehydration stress ( Ye et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The TIFY family was divided into TIFY , Jasmonate ZIM (JAZ), ZIM-like (ZML), and PEAPOD (PPD) subfamilies. A previous genome-wide analysis identified 34 TIFY genes in G. soja ( Zhu et al., 2013 ), and a recent study reported 38 TIFY genes in G. max ( Liu X. et al., 2022 ). In G. soja , GsTIFY10s (10a, 10b, 10c, 10d, 10e, and 10f) and GsTIFY11s (11a and 11b) shared the highest sequence identity and were clustered together in the JAZ subfamily.…”
Section: Transcription Factors Regulating Salt-alkaline Stress Respon...mentioning
confidence: 93%